Analisis tidak Centernya Shaft pada Kinerja Cargo Oil Pump di Kapal MT. Kurau - Rochmad Hidayat; Muhammad Darwis; Indah Ayu Johanda Putri; Agus Prawoto; Frenki Imanto; Shofa Dai Robbi (Pusat riset dan Inovasi Nasional, 2025)
This study discusses the causes of leakage in cargo oil pumps, which play a crucial role in the discharge operation of tankers carrying oil, chemicals, and gas. Regular maintenance is essential to prevent damage that could hinder the ship's operations. The method used is descriptive qualitative, with data gathered from observations, interviews, documentation, and literature review. The analysis is conducted using Fishbone to identify the root causes of the problem. The results show that leakage occurs due to the misalignment of the pump shaft. This misalignment causes excessive vibration at high speeds, damaging components, especially the carbon seal face of the mechanical seal, leading to leakage of cargo. Preventive measures include regular and scheduled maintenance, proper lubrication, routine inspection while the pump is running, and alignment checks to ensure the shaft is straight. If any issues are found, repair or replacement with new parts is necessary to ensure the pump operates efficiently and the discharge process runs smoothly.